453 Long-Term Outcomes Following Minimally Invasive Laminectomy for the Treatment of Lumbar Synovial Cysts. (1st April 2022) - Chesney, Kelsi; Elsouri, Mohamad; Stylli, Jack; Phelps, Emily; Fayed, Islam; Voyadzis, Jean-Marc; Sandhu, Faheem A.
Abstract : INTRODUCTION: Lumbar synovial cysts (LSC), most often occurring at L4-5, can cause painful radiculopathy and/or sensory or motor deficits when symptomatic. The etiology of these lesions is thought to be related to degeneration of the facet joints. Historically, the first-line surgical treatment has been decompression with fusion. More recently, minimally invasive laminectomy without fusion has been shown to achieve equal or superior results to traditional decompression and fusion methods. METHODS: A retrospective review was performed at a single institution, over a 10-year period, of patients undergoing minimally invasive laminectomy for symptomatic LSCs. The primary outcome in this study was the rate of revision surgery requiring fusion. Secondary outcomes were based on analysis of baseline patient characteristics, operative details, and postoperative outcomes. RESULTS: Eighty-five patients with symptomatic LSC underwent minimally invasive laminectomy alone from January 2010 to August 2020 at our institution. The most common location was L4-5 (71%), followed by L5-S1 (17%), and then L3-4 (11%). The average patient was 65 years old with a BMI of 28.6. All patients (100%) presented with symptoms of painful radiculopathy. Pre-operative imaging identified spondylolisthesis in 44 (57%) patients, none of which were considered unstable on dynamic X-rays. Average length of the procedure was 93 minutes, with 78% of patients discharged home on the same day of their procedure. There was only one reported intraoperative durotomy. Over 45 months of mean follow-up, seventeen patients (20%) required eighteen revision operations. Of those, 15 were primary spinal fusions (17.6%), 2 were washouts for epidural hematoma (2.4%), and 1 was a revision decompression for recurrent cyst (1.2%). Mean time to fusion surgery was 31 months. There were no identifiable risk factors on multivariate regression analysis that predicted the need for fusion. CONCLUSION: After minimally invasive laminectomy for lumbar synoval cyst, only 18% of the 85 patients in our cohort went on to require a fusion over a ten-year period.